Management of recurrent aggressive vertebral hemangiomas: a comparative study of piecemeal intralesional spondylectomy and modified total en bloc spondylectomy - Dongjie Jiang; Zihuan Zhou; Qi Zhang; Shaohui He; Haitao Sun; Xiaopan Cai; Tielong Liu; Xinghai Yang; Haifeng Wei; Jianru Xiao (BMC Surgery)
Abstract Background The management of recurrent aggressive vertebral hemangiomas (AVHs) with neurological deficits poses a challenge due to their profuse vascularization and propensity for recurrence. The optimal approach to managing recurrence AVHs remains a topic of debate within the academic community. Methods A retrospective analysis was conducted on a cohort of patients who experienced recurrent AVH in the thoracic and lumbar spine at our institution from August 2015 to July 2022. A total of 31 patients, underwent treatment with either piecemeal intralesional spondylectomy (PIS) or modified total en bloc spondylectomy (MTES). Clinical documentation and surgical outcomes, including pre- and postoperative neurological function assessed by the American Spinal Injury Association (ASIA) score, Numeric Rating Scale (NRS), surgical duration, blood loss, recurrence rate, and complications, were retrospectively presented and analyzed. Results The study followed a cohort of 16 males and 15 females with recurrent AVHs in the thoracic or lumbar spine for a period ranging from 12 to 106 months. All patients presented with neurological deficits, with 20 patients undergoing PIS and 11 patients undergoing one-stage MTES. Both treatment modalities resulted in significant reductions in pain-NRS and ASIA scores. The MTES group experienced less intraoperative blood loss compared to the PIS group. During the follow-up period, four patients in the PIS group experienced recurrence. No serious complications or evidence of internal fixation failure were observed. Conclusions The modified TES technique presents a comprehensive resection, less blood loss, lower incidence of recurrence, and effective tumor control for recurrent AVHs in thoracic and lumbar spine through post-only approach.